2022
DOI: 10.3390/ijms23147780
|View full text |Cite
|
Sign up to set email alerts
|

Potent CCR3 Receptor Antagonist, SB328437, Suppresses Colonic Eosinophil Chemotaxis and Inflammation in the Winnie Murine Model of Spontaneous Chronic Colitis

Abstract: Eosinophils and their regulatory molecules have been associated with chronic intestinal inflammation and gastrointestinal dysfunctions; eosinophil accumulation in the gut is prominent in inflammatory bowel disease (IBD). The chemokine receptor CCR3 plays a pivotal role in local and systemic recruitment and activation of eosinophils. In this study, we targeted CCR3-ligand interactions with a potent CCR3 receptor antagonist, SB328437, to alleviate eosinophil-associated immunological responses in the Winnie model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 133 publications
0
9
0
Order By: Relevance
“…Recent studies have shown that colitisassociated activation of neutrophils, macrophages, B-and T-cells, broblasts, endothelial cells and platelets, and hypoxic stress caused a down-regulation of mitochondrial proteins while pro-in ammatory proteins were known to be upregulated by immune cells, the colitis-associated epithelial cells, broblasts, endothelial cells and platelets contributed towards anti-in ammatory and wound healing-promoting proteins [45]. Further, there is an increase in eosinophils in IBD both in mice and in humans, which can be alleviated with anti-CCR3 receptor antagonists [20,46,47]. The fact that several of these alterations resemble abnormal motor capabilities in patients with IBD further exempli es that the Winnie mouse model is remarkably similar to human IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that colitisassociated activation of neutrophils, macrophages, B-and T-cells, broblasts, endothelial cells and platelets, and hypoxic stress caused a down-regulation of mitochondrial proteins while pro-in ammatory proteins were known to be upregulated by immune cells, the colitis-associated epithelial cells, broblasts, endothelial cells and platelets contributed towards anti-in ammatory and wound healing-promoting proteins [45]. Further, there is an increase in eosinophils in IBD both in mice and in humans, which can be alleviated with anti-CCR3 receptor antagonists [20,46,47]. The fact that several of these alterations resemble abnormal motor capabilities in patients with IBD further exempli es that the Winnie mouse model is remarkably similar to human IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Slides were then mounted with DPX mounting media (Sigma-Aldrich #03989). A histological grading system was used to evaluate gross morphological damage using the following parameters: aberrant crypt architecture (score range, 0–3), crypt abscesses (0–3), leukocyte infiltration (0–3), epithelial damage (0–3), and ulceration (0–3); an average of 3 areas of 500 × 500 µm per section were analysed [ 4 , 5 ]. Slides were imaged using an Olympus BX53 microscope (Olympus Imaging, Sydney, NSW, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…HMGB1 has emerged as an important alarmin to cellular stress involved in the pathophysiology of several diseases [ 3 ]. In conditions of cellular stress, the two HMGB1 nuclear localization sites are hyperacetylated, and HMGB1 translocates to the cellular cytoplasm, where it is released actively by leukocytes or passively by necrotic and necroptotic cells [ 4 ]. In the extracellular space, HMGB1 functions as a damage-associated molecular pattern (DAMP), acting as a direct chemoattractant via the C-X-C chemokine ligand 12 (CXCL12) and C-X-C chemokine receptor 4 (CXCR4) axis, as well as stimulating the release of pro-inflammatory mediators via toll-like receptors (TLR)-2 and TLR-4 expressed on nearby immune cells [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils are not only involved in inflammation but also induce alterations to the enteric nervous system and are linked with disease severity [ 69 ]. The chemokine receptor, CCR3 which plays a role in the recruitment and activation of eosinophils has been shown that its blockade via a CCR3 antagonist attenuates disease severity and morphological damage to inflamed intestinal tissues in the spontaneous model of chronic colitis ( Winnie mice) [ 70 ]. Similarly, in guinea pigs, intestinal inflammation/colitis caused following TNBS treatment results in increase of eosinophils at the site of inflammation.…”
Section: Inflammatory Mediators In Inflammatory Bowel Diseasementioning
confidence: 99%